Scalable product platform design based on design structure matrix and axiomatic design. (2015) - Cheng, Xianfu; Lan, Guangying; Zhu, Qihang
Product platform design has been recognised as an effective means to establish and preserve competitive status in the market and to maintain the economies of scale and scope, while keeping production costs to a minimum. To this end, a new design method for scalable product platform is presented based on design structure matrix and axiomatic design. Initially in this process, the customer needs are analysed, and then the common and individual needs are identified. Second, the key functional requirement parameters are extracted and mapped. Next, a design matrix is established. The functional structure decomposition figure and the design matrix are combined for constructing a design structure matrix. Then, an extension clustering algorithm is utilised to cluster the elements, and then common variants and adjustable variants of product platform are recognised reasonable. Afterwards, a product platform design scheme based on a design structure matrix and axiomatic design is determined. Finally, a product platform on electro-hydraulic drum brakes is developed. The results demonstrate the effectiveness and practical value of the new design method.